The role of noncoding RNA and its diagnostic potential in intrahepatic cholestasis of pregnancy: a research update - Xiong, Liling; Tang, Mi; Xing, Shasha; Yang, Xiao (Frontiers in Genetics, 2023)
Intrahepatic cholestasis of pregnancy (ICP) is a common liver disorder that generally occurs during the second or third trimester of pregnancy. It rarely causes any harm to the mother; however, it can result in short-and long-term complications in the offspring.Therefore, it is crucial to diagnose and treat this condition to avoid poor pregnancy outcomes. The identification of novel markers with potential diagnostic, prognostic, and therapeutic utility in ICP has gained attention. Noncoding RNAs (ncRNAs), including microRNA, long noncoding RNA, and circular RNA, are a type of transcripts that are not translated into proteins. They possess vital biological functions, including transcriptional and translational regulation and DNA, RNA, and protein interactions.The pathogenesis of ICP is related to the aberrant expression of several circulating or placenta-related ncRNAs. In this review, we summarized all recent findings on ncRNAs and ICP and outlined the concepts that form the basis for the early diagnosis and targeted treatment of ICP.